Free and conjugated phenolic compounds and their antioxidant activities in regular and non-darkening cranberry bean (Phaseolus vulgaris L.) seed coats. (October 2015) - Chen, Peter X.; Bozzo, Gale G.; Freixas-Coutin, José A.; Marcone, Massimo F.; Pauls, Peter K.; Tang, Yao; Zhang, Bing; Liu, Ronghua; Tsao, Rong
Highlights: Complete profiles of soluble phenolics of regular- and non-darkening cranberry bean seed coats. Significantly higher overall phenolic content in regular-darkening seed coats. First identification of individual flavonoids in cranberry beans. Prevalence of catechin and other monomeric and oligomeric flavonoids in RD beans. Strong ORAC and FRAP antioxidant activity exhibited by extracts of RD beans over ND. Abstract: Postharvest darkening in dry bean ( Phaseolus vulgaris L.) negatively impacts consumer preference. Regular-darkening (RD) and non-darkening (ND) cranberry beans were profiled for seed coat phenolics using HPLC–DAD/LC–ESI–MS n and assessed for antioxidant activity using oxygen radical absorbing capacity (ORAC) and ferric-reducing antioxidant power (FRAP) assays. Flavonoids were exclusive to free phenolic extracts of RD beans. Total phenolic content (TPC) was significantly higher ( p < 0.05) in RD seed coats (52.41–56.43 mg GAE/g) compared to ND seed coats (2.00–2.06 mg GAE/g). Alkaline hydrolysis revealed the presence of phenolic acids and flavonoid conjugates in RD beans. Only p -coumaric and ferulic acids were found in ND beans. Overall antioxidant activity was stronger in RD seed coats (125.28–287.87 µmole TE/g and 20.71–54.01 µmole AAE/g) compared to ND seed coats (2.11–10.09 µmole TE/g and 0.73–1.88 µmole AAE/g). This is the first report of specific flavonoids in cranberry beans.